The school-home connection : forging positive relationships with parents - Olender, Rosemary A.; Elias, Jacquelyn; Mastroleo, Rosemary D. (Corwin, a Sage Publications Company, 2010)
Drawing on original research and the authors' professional experiences, this resource presents a comprehensive approach to developing more positive relationships with students and their families.